Career and Entrepreneur Carnival offers job opportunities - UMP, PNC
Universiti Malaysia Pahang (UMP)’s Student Affairs and Alumni (SAFFAD) and Pahang Labour Department organised a three-day Career and Entrepreneur Carnival (CEC) held at Megamall Shopping Complex in Kuantan on October 15, 2011.